Nutritional Evaluation of Earthworm Powder (Lampito mauritii) - A. J. Bhorgin Lourdumary and K. Uma (Journal of Applied Pharmaceutical Science, 2013)
Dried earthworm powder from culture of Lampito mauritii in vermicomposting units and subjected to analysis of protein, carbohydrate and mineral content. The EWP contained large amounts of protein (31.7 % ), iron (241.1ppm), soluble nitrogen (1.8%), zinc (32.34ppm), manganese (17.2ppm) and copper (4.501ppm) together with notable quantities of potassium, calcium, magnesium, phosphorus and carbohydrate indicating that this type of earthworm contain potentially useful quantities of many nutrients, that are important to the human health .
Keywords: Protein, Carbohydrate, Mineral, Lampito mau